Effect of Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior at PDAM Head Office Majalengka Regency - Haris Fauzi (Enrichment : Journal of Management, 2021)
This research was conducted at the Central PDAM of Majalengka Regency. The purpose of this study was to determine how large the influence of job satisfaction and organizational commitment on organizational citizenship behavior either partially or simultaneously. In this study, the author uses a survey method with descriptive analysis techniques and verification. The data collection technique was done by giving a questionnaire. Testing of research instruments is done by testing the validity and reliability testing using a Likert scale. The data analysis tool uses classical assumption test, multiple linear regression analysis, coefficient of determination analysis, t test and f test. The results of this study indicate that job satisfaction is included in the high category. Organizational commitment is included in the high category. Organizational citizenship behavior is included in the high category. Job satisfaction has a positive and significant effect on organizational citizenship behavior. Organizational commitment has a positive and significant effect on organizational citizenship behavior. Job satisfaction and organizational commitment together have a positive and significant effect on organizational citizenship behavior.